Development of an Electric Car Power Management and Monitoring System (International Journal of Food and Nutritional Sciences, 2022)
The adoption of electric vehicles has been growing rapidly in recent years. However, battery-relatedissues, such as limited range and battery degradation, have been hindering the wider adoption ofelectric cars. This research presents the development of an electric car power management andmonitoring system that accurately forecasts the residual service life of the battery and realizes thedynamic management of the running power condition of the electric car.